ANALYSIS OF TOоTH PROFILE AND MESHING CHARACTERISTICS OF DOUBLE CYCLOID PIN GEAR TRANSMISSION - CUI JianKun; DING JiaLe; SHI YuHeng; ZHANG DeQi (Jixie qiangdu)
The double cycloid tooth profile was applied to the NN type planetary gear transmission with small tooth difference. By analyzing the concavity, curvature and radius of curvature of the inner and outer cycloid tooth profile, the characteristics of the inner and outer cycloid tooth profile were obtained. Through the graphic method, the calculation formula ofthe pressure angle of the inner and outer cycloid gears in the double cycloid pin gear transmission was derived, and the variation law of the pressure angle in the meshing process and the influence of the main parameters of the double cycloid pin gear on the pressure angle of the inner and outer cycloid gears were obtained. Through the study of equidistant modification and shift modification, it is shown that the tooth profile modification has a significant impact on the tooth profile.